Grinberg, Miguel. 2008. Cómo vino la mano. Orígenes del rock argentino: Buenos Aires: Gourmet Musical, 296 pp. (Revista Argentina de Musicología, 2018)
Review: Grinberg, Miguel. 2008. Cómo vino la mano. Orígenes del rock argentino. Buenos Aires: Gourmet Musical, 296 pp.